THE EFFECT OF SELF-CONTROL ON THE WORKLOAD OF TAKALAR 2 TAKALAR SMA STATE TEACHERS - Jam'an, Jam'an; Nurbaya, Sitti; Azis, Astriningsih (Jurnal Ekonomi Balance, 2019)
This study aims to determine the effect of self control on the workload of teachers in SMA Negeri 2 Takalar. This type of research used in this research is quantitative research. The data collection technique used is a questionnaire or questionnaire by collecting data or information and stating the variables that describe the teachers' perceptions of the workload itself. With a total sample of 85 respondents drawn from the entire population. The results showed that the value of tcount 2.308 > ttable 1.98827 with a significant value of 0.023 < 0.05 and a positive regression coefficient value of 0.197. Thus H0 is rejected and Ha is accepted, which means that the variable X has a significant positive effect on variable Y in other words, self control has a significant positive effect on the workload of teachers in SMA Negeri 2 Takalar.